Mash1 expression is induced in neuroendocrine prostate cancer upon the loss of Foxa21. Issue 6 (11th October 2012) - Gupta, Aparna; Yu, Xiuping; Case, Tom; Paul, Manik; Shen, Michael M.; Kaestner, Klaus H.; Matusik, Robert J.
Abstract Neuroendocrine (NE) prostate tumors and neuroendocrine differentiation (NED) in prostatic adenocarcinomas have been associated with poor prognosis. In this study, we used the TRAMP mouse model that develops NE prostate tumors to identify key factors that can lead to NED. We have previously reported that NE tumors express the forkhead transcription factor, Foxa2, Mash1 (mouse achaete scute homolog‐1), as well as Synaptophysin. In TRAMP, the prostatic intraepithelial neoplasia (PIN) first expresses Foxa2 and Synaptophysin, which then progresses to NE cancer. In order to determine if Foxa2 is dispensable for development or maintenance of NE cancer, a conditional knock‐out of Foxa2 in TRAMP mice was generated by breeding mice with two floxed alleles of Foxa2 and one copy of Nkx3.1‐Cre. Nkx3.1‐Cre/Foxa2loxP/loxP mice showed loss of Foxa2 expression in embryonic prostatic buds. No expression of Foxa2 was seen in the adult prostate in either conditional null or control mice. Foxa2 is universally expressed in all wild type TRAMP NE tumors, but Mash1 expression is seen only in a few samples in a few cells. With the loss of Foxa2 in the NE tumors of the TRAMP/Nkx3.1‐Cre/Foxa2loxP/loxP mice, the expression of the pro‐neuronal gene Mash1 is upregulated. NE tumors from both the TRAMP control and Foxa2‐deficient TRAMP prostate express Synaptophysin and SV40 Large T‐antigen, and both show a loss of androgen receptor expression in NE cells. These studies suggest that the TRAMP NE tumors can form in the absence of Foxa2 by an up regulation of Mash1. Prostate 73: 582–589, 2013. © 2012 Wiley Periodicals, Inc.